1984
DOI: 10.1111/j.1476-5381.1984.tb10079.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent relaxation induced by angiotensin II and histamine in isolated arteries of dog

Abstract: 1In helical strips of dog renal and mesenteric arteries pre-contracted with prostaglandin F2X (PGF2<,), endothelium-dependent relaxations were investigated. Removal of the endothelium was shown histologically by staining with silver nitrate and functionally by testing the inability of acetylcholine to induce arterial relaxations. 2 When the endothelium was removed, relaxation of renal arteries to angiotensin (Ang) II was markedly suppressed, whereas relaxations induced by PGI2 or isoprenaline were attenuated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
5
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(32 citation statements)
references
References 18 publications
0
26
5
1
Order By: Relevance
“…Contrary to these findings, Ang II itself has been associated with significant induction of NOS activity in ECs and subsequent increases in cGMP production in VSMC. Several studies have shown that the endothelium can modulate Ang II-induced contraction or vasodilatation of blood vessels in some vascular beds under certain circumstances (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these findings, Ang II itself has been associated with significant induction of NOS activity in ECs and subsequent increases in cGMP production in VSMC. Several studies have shown that the endothelium can modulate Ang II-induced contraction or vasodilatation of blood vessels in some vascular beds under certain circumstances (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Early experiments demonstrate that histamine-induced vasodilation is dependent on intact endothelium containing eNOS which suggests that histamine's action is at least partly mediated through nitric oxide [51,52]. Further evidence to support the role of the NO-cGMP pathway in anaphylaxis is demonstrated by the finding that increased histamine results in upregulation of eNOS gene expression with increased production of NO leading to vasodilation through increased activity of GC.…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 99%
“…There was a significant treatment-by-dose interaction, suggesting receptor-stimulated dose-dependent release of a vasodilator PG. Other vasoconstrictors such as angiotensin II also release a vasodilator PG (Toda, 1984). Endothelial cells are known to respond to changes (Rubanyi, 1991;Davies & Tripathi, 1993) (Miller, 1991).…”
Section: Discussionmentioning
confidence: 99%